Game-based congestion-aware routing algorithm in wireless network on chips. (20th April 2023) - Tahanian, Esmaeel; Tajary, Alireza; Rezvani, Mohsen
Wireless network on chip (WiNoC) has been introduced to alleviate some challenges with conventional NoC such as high latency and power consumption. Routing the packet through the wireless links for arriving to far apart destination leads to a shorter path. Therefore, many of nodes prefer to send their packets to nearest wireless router on the WiNoC. When the demand for a wireless node increases, the likelihood of the congestion increases. To address this problem, we propose a game-based yet simple routing algorithm to balance the traffic in this paper. The WiNoC is modelled with a mixed-strategy Bayesian-game in which the nodes are the players with two valid actions namely, routing the packets with and without the wireless links. The simulation results show that using the proposed mixed-strategy for considerably improves the performance of the network, more precisely, the system performance is improved 10%-42% compared with the previous related works.